• Angabe:


    Man löse die Differentialgleichung durch Trennung der Veränderlichen.


    cosydx+(1-e^-x)sinydy=0 (für x=0 sei y=Pi/4)


    Lösung:


    -(1-e^-x)sinydy=cosydx
    -sinydy/cosy=1/1-e^-x dx


    siny/cosy=tany


    Int...Integral


    -Int tanydy = Int 1/1-e^-x dx


    NR...Nebenrechnung


    NR: 1-e^-x=e^x * e^-x - e^-x = e^-x * (e^x - 1)


    -Int tanydy= Int 1/e^-x * (e^x - 1) dy


    e^x-1=u
    e^xdx=du
    dx=du/e^x


    ln|cosy|=Int du/u
    ln|cosy|=ln|u|
    ln|cosy|=ln|e^x-1|+c
    cosy=(e^x-1)*e^c
    e^c=d
    y=arccos[(ex-1)*d]